The Role of Genetic Polymorphisms in High-Dose Methotrexate Toxicity and Response in Hematological Malignancies: A Systematic Review and Meta-Analysis - Song, Zaiwei; Hu, Yang; Liu, Shuang; Jiang, Dan; Yi, Zhanmiao; Benjamin, Mason M.; Zhao, Rongsheng (Frontiers in Pharmacology, 2021)
Objective: High-dose methotrexate (HDMTX) is a mainstay therapeutic agent for the treatment of diverse hematological malignancies, and it plays significant inter-individual variability regarding the pharmacokinetic and toxicity. The genetic association of HDMTX has been widely investigated, but the conflicting results have complicated the clinical utility. Therefore, this systematic review aims to determine the role of gene variants within the HDMTX pathway, and to fill the gap between knowledge and clinical practice. Methods: Databases including EMBASE, Pubmed, Cochrane Central Register of Controlled Trials (CENTRAL) and the Clinical Trials.gov were searched through November 2020. We included twelve single nucleotide polymorphisms (SNPs) within HDMTX pathway, involving RFC1, SLOC1B1, ABCB1, FPGS, GGH, MTHFR, DHFR, TYMS and ATIC. Meta-analysis was conducted by using Cochrane Collaboration Review Manager software 5.3. The odds ratios (OR) or hazard ratios (HR) with 95% conﬁdence interval (95% CI) were analyzed to evaluate the associations between SNPs and clinical outcomes. This study was performed according to the PRISMA guideline. Results: In total, 34 studies with 4102 subjects were identified for the association analysis. Nine SNPs involving MTHFR, RFC1, ABCB1, SLOC1B1, TYMS, FPGS, ATIC genes were investigated, while none of studies reported the polymorphisms of GGH and DHFR yet. Two SNPs were statistically associated with the increased risk of HDMTX toxicity: MTHFR 677C>T and hepatoxicity (dominant, OR =1.52, 95% CI=1.03-2.23; recessive, OR=1.68, 95% CI=1.10-2.55; allelic, OR=1.41, 95% CI=1.01-1.97), mucositis (dominant, OR=2.11, 95% CI=1.31-3.41; allelic, OR=1.91, 95% CI=1.28-2.85), and renal toxicity (recessive, OR=3.54, 95% CI=1.81-6.90; allelic, OR=1.89, 95% CI=1.18-3.02); ABCB1 3435C>T and hepatoxicity (dominant, OR=3.80, 95% CI=1.68-8.61). Whereas a tendency toward the decreased risk of HDMTX toxicity were present in three SNPs: TYMS 2R>3R and mucositis (dominant, OR=0.66, 95% CI=0.47-0.94); RFC1 80A>G and hepatotoxicity (recessive, OR=0.35, 95% CI=0.16-0.76); MTHFR 1298A>C and renal toxicity (allelic, OR=0.41, 95% CI=0.18-0.97). Since the data of prognosis outcomes were substantially lacking, current studies were underpowered to investigate the genetic association. Conclusions: We conclude that genotyping of MTHFR and/or ABCB1 polymorphisms prior to treatment, MTHFR 677C>T particularly, is likely to be potentially useful with the aim of tailoring HDMTX therapy and thus reducing toxicity in patients with hematological malignancies.